Climate, war conflict and social burden for food and nutritional security in Mali: Impact of local aid efforts - Dao, Omar (2025)
Background: Food insecurity grow in the shadow of social deferment, climate change and war conflicts, all variables that converge in Mali. To determinate food security status & impact of local aid in Mali`s, we performed the present study. Methods: A description of actual situation in households (after 1 year of international aid), was compared with former evaluation obtained during 2021 using a questionnaire that detect household socio-economic and an anthropometric measurements of house members. The study period was 1-1-2022/1-1-2023. Results: A total of 340 households were surveyed (2503 members). Male represented 49% (n:1228) and female 51% (n:1275) while 118 pregnant and 217 breastfeeding). International NGO aid and local government support to households obtained an improvement in certain indicators in relation to the baseline measurement surveyed in 2021. This improvement was reflected in the access to drinking water (7 L/day more than 2021) while the water point was located inside the house in 50.1% of households (29.1% in 2021). Food insecurity was 15.6% on average (21.1% in 2021). The strategies followed by households were adapting meals volumes (in 71.2% of households), opting for less expensive food (in 28% of the cases) or transferring the adult food ration to children (19% of the families). 33.3% of households received assistance in the last 6 months (37% food-assistance; 19.7% free-medicines, 16.5 free-money transfer). On contrary, certain economic activities like fishing, drastically drop from 70% in 2021 to 38% in 2022. Conclusion: Armed conflicts in the north-west region of Mali (circles of Goundam/Timbuktu) have had a negative impact on the quality and living conditions of the inhabitants of the area. Local and international support helped to mitigate the harmful consequences of the war, especially in terms water and food access. Some economic activities that help to sustain households, such as fishing, continue to decline.